Faculty attendance system using Geofence, Face-recognition and admin portal - Anandteertha Rao , Atharva Vaidya , Yagnesh Narayanan , (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2022)
Attendance is the most common element throughout our life, starting from schooling days, right to the corporate world. Even though throughout the past few decades a lot of modifications and improvements have been made in the attendance monitoring system, there has always been a few setbacks. Our solution, provides an efficient and a very way to provide attendance in any organization, without using the biometric which tends to be a huge investment and during the pandemic situation, such as the one we are facing now, we can never be too careful. We use face recognition, geofencing and an admin portal to provide three most effective and easy ways for any user to mark their attendance